Binomial sums whose coefficients are products of terms of binary sequences - Kiliç, Emrah,; Ömür N.Ȩ.E.,; Türker Uluta̧ Y., (Utilitas Mathematica, 2011)
In this study, we introduce sums and alternating sums of products of terms of sequences Ukn and (Vkn) with binomial coefficents. These sums have a nice representation for the terms of sequences U kn and Vkn.